Synergies and Conflicts: Examining the Effects of Mandatory Disclosure Rules on Corporate Governance Structures and Functions with Audit Committee as a Moderating Variable - Dian Sulistyorini Wulandari; agus Fuadi; Diana Anggraeni (Pusat P2M Politeknik Negeri Batam, 2024)
This study explores the complex interactions between mandatory disclosure rules and corporate governance structures, focusing on the moderating role of audit committees. While mandatory disclosure rules aim to enhance transparency and accountability, their implementation can create both synergies and conflicts within corporate governance frameworks. This research examines how these regulations influence governance structures and functions, particularly regarding board dynamics, managerial behavior, and shareholder relations. By introducing the audit committee as a moderating variable, the study investigates whether its presence strengthens or mitigates the effects of mandatory disclosure on corporate governance effectiveness. The findings highlight the dual nature of these regulations